THE EFFECT OF STUDENTS' RESPONSE IN USING PROBLEM BASED LEARNING WITH SIMULATION TOWARD STUDENTS' ACHIEVEMENT (LIGHT CONCEPT) - Ary Norsaputra; Johansyah Johansyah (Proceedings of the International Conference on Applied Science and Health, 2017)
Background: In many circumstances, students’ alternative conception on light concepts have encountered in previous studies. One of the causes factor is the lack of students’ response, and it may allow student to have a low achievement. According to Educational Unit Level Curriculum (KTSP), an active learning such as Problem Based Learning (PBL) can help students meet high achievement. In addition, learning through simulation is also increased students’ response. Aims: Based on rationale of this study, we concern to see the effect of students’ response toward students’ achievement in learning physics through PBL with simulation. Methods: There were 27 grades eighth students had been involved as participants. This study had been conducted by posttest only control design, and quantitative analysis had been used to analyze the data. Twenty items of questioner of students’ response, and twenty item of posttest of light concept had been applied to gather data. Results: Our findings revealed that students who have learned by PBL with simulations have shown a great response with score 76.37 %. The students’ achievements have exceeded the minimum completeness criteria (KKM) with the score 73.15 > 70. However, the correlation of students’ response towards students’ achievement is very low with the correlation value ???? = 0.1801.Moreover, it merely 3.2 % of students’ achievement is influenced by learning trough PBL with simulations. Conclusion: In short, leaning through PBL with simulation allows students to have a great response, but they aren’t giving a significant effect to the students achievement, and it should be another factor that we missed.